1-Hydroxyethylidene-1, 1-diphosphonic acid (HEDP)-Zn complex thin films for the corrosion protection of cold-rolled steel (CRS). (15th August 2019) - Yan, Ru; Gao, Xiang; He, Wei; Chen, Ting; Ma, Houyi
Highlights: The self-strengthening HEDP-Zn films were constructed on CRS surface. The HEDP-Zn films can quickly increase corrosion resistance under NaCl environment. Self-strengthening performance is a feature of HEDP-Zn films. Self-strengthening performance was related to film formation time. The possible self-strengthening mechanism was proposed. Abstract: Self-strengthening HEDP-Zn films were constructed on the CRS surface and the corrosion protection was afforded by electrochemical impedance spectroscopy (EIS) tests. After immersion in NaCl solution, HEDP-Zn-coated CRS underwent three stages: strengthening, balance and weakening. During immersion, a portion of unstable HEDP-Zn complexes were destroyed, accompanied by the intercalation and departure of Na +, thereby resulting in the changes in microstructure, chemical compositions and thickness of the films. Thus, anticorrosion performance increased due to the increased surface coverage by the complexes and additional binding sites during the first stage but decreased because of the reduced film thickness in the third stage.